Rozwijanie sprawności pisania obcojęzycznego na przykładzie polsko-niemieckiego internetowego projektu tandemowo-tridemowego „Schreiben(üben) im e-Tandem/e-Tridem” – możliwości i ograniczenia - Pawłowska-Balcerska, Agnieszka (Neofilolog, 2021)
Although in the age of media writing is experiencing a kind of renaissance, and young people cannot imagine everyday life without texts, e-mails, online discussion forums or virtual instant messaging, writing as part of institutionalized teaching evokes rather negative associations among many learners. Therefore, based on the example of the Polish-German online tandem-tridem project, an attempt will be made in this article to answer the following questions: How can one draw on the positive, out-of-school experiences of learners with (foreign) writing in foreign language classes? How can they be used in the institutionalized process of teaching and learning foreign languages while developing writing skills? What advantages and dangers are associated with the mentioned activities?